The Benefits of Living With Close Others: A Longitudinal Examination of Mental Health Before and During a Global Stressor. (November 2022) - Sisson, Natalie M.; Willroth, Emily C.; Le, Bonnie M.; Ford, Brett Q.
For better or worse, the people one lives with may exert a powerful influence on one's mental health, perhaps especially during times of stress. The COVID-19 pandemic—a large-scale stressor that prompted health recommendations to stay home to reduce disease spread—provided a unique context for examining how the people who share one's home may shape one's mental health. A seven-wave longitudinal study assessed mental health month to month before and during the pandemic (February through September 2020) in two diverse samples of U.S. adults ( N = 656; N = 544). Preregistered analyses demonstrated that people living with close others (children and/or romantic partners) experienced better well-being before and during the pandemic's first 6 months. These groups also experienced unique increases in ill-being during the pandemic's onset, but parents' ill-being also recovered more quickly. These findings highlight the crucial protective function of close relationships for mental health both generally and amid a pandemic.